TRANSFORMASI LEMBAGA KEUANGAN NON BANK ISLAM DALAM MENINGKATKAN INKLUSI KEUANGAN BERBASIS PRINSIP SYARIAH NASIONAL INDONESIA - Anggi Arko Azzahra Kudadiri; Aida Fadillah; Muhammad Arfan Harahap (CV. Barokah Publsiher, 2025)
This research discusses the role and development of Islamic Non-Bank Financial Institutions within the modern economic system based on sharia principles. Islamic Non-Bank Financial Institutions emerge as alternative financial intermediaries that not only focus on profit generation but also emphasize justice, social welfare, and ethical balance. This research aims to analyze the characteristics, functions, and contributions of Islamic Non-Bank Financial Institutions in supporting economic growth and financial inclusion. The method used in this research is a literature study by examining relevant books, scientific journals, and regulations related to Islamic finance. The results indicate that Islamic Non-Bank Financial Institutions play a strategic role in providing sharia-compliant financial services such as financing, Islamic insurance (takaful), Islamic pension funds, and other financing institutions. Their existence enhances public access to halal and ethical financial services. However, these institutions face several challenges, including low levels of sharia financial literacy and strong competition from conventional financial institutions. Therefore, strengthening regulations, encouraging product innovation, and improving continuous education are necessary to ensure the sustainable development of Islamic Non-Bank Financial Institutions in the future.